2018
DOI: 10.3390/ijerph15112548
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices about Zika among a University Community Located in an Endemic Zone in Mexico

Abstract: To assess the knowledge, attitudes, and practices about the Zika virus in both students and workers at the University of Veracruz, an online survey was conducted. The participants were divided into two groups: one according to sex, the other according to whether they were workers or students. Their answers were classified into knowledge, attitudes, and practices and they were rated as low, medium, and high. The results showed that knowledge about Zika prevailing among the university population is considered as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
(28 reference statements)
4
11
0
Order By: Relevance
“…This highlights the inadequacy of current public health measures and the need for improved means of communication to the general public. Paralleling findings from other studies [ 29 , 30 , 31 ], the transmission of ZIKV by an insect vector was known to a greater number of subjects than were the perinatal and sexual transmission pathways. The use of repellents by approximately half of the participants was similar to previous studies of pregnant women conducted in Martinique (49.5%) [ 32 ] and Brazil (56%) [ 33 ] and different from what was found in the US Virgin Islands, where 74% of the pregnant women reported using repellent [ 34 ].…”
Section: Discussionsupporting
confidence: 71%
“…This highlights the inadequacy of current public health measures and the need for improved means of communication to the general public. Paralleling findings from other studies [ 29 , 30 , 31 ], the transmission of ZIKV by an insect vector was known to a greater number of subjects than were the perinatal and sexual transmission pathways. The use of repellents by approximately half of the participants was similar to previous studies of pregnant women conducted in Martinique (49.5%) [ 32 ] and Brazil (56%) [ 33 ] and different from what was found in the US Virgin Islands, where 74% of the pregnant women reported using repellent [ 34 ].…”
Section: Discussionsupporting
confidence: 71%
“…The results of KAP surveys help create culturally-competent interventions that are specific to the affected community [8]. Recently, in Latin America, KAP surveys have been used to assess knowledge, attitudes, and practices and inform interventions for Dengue, Zika, Chikungunya, and Malaria [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…2018 emphаsized that the correlation between knowledge and prаctices show а discrepancy, suggesting that аlthough people hаve knowledge about the risk of ZIKА infection, proper preventive meаsures are not tаken (p < 0.001). [86] In contrаst to this study, Nelson E. 2018 observed that the sexuаl prevention methods were more likely to be used by individuаls who reported hаving knowledge of the sexuаl trаnsmissibility of ZIKА thаn those who did not hаve this knowledge. [87] Our findings аre similаr to other ZIKА KАP surveys аlthough it should be noted thаt they were conducted аmong pregnаnt women.…”
Section: Discussionmentioning
confidence: 68%